Syntheses, spectral characterization, single crystal X-ray diffraction and computational in gas and solid phases studies on chloro- acetic acid N? -(2-hydroxy-naphthalen- 1-ylmethylene)- N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazide - Karakurt, Tuncay; Dincer, Muharrem; Cukurovali, Alaaddin (Springer Int Publ Ag, 2020)
In this study, the molecular structure of single crystal containing Schiff bases has been characterized by X-ray diffraction, NMR, IR and UV-Vis spectral techniques and compared with similar molecules in the literature. For the purpose of supporting X-ray results, geometric parameters and spectroscopic studies of the title compound were theoretically performed by Hartree-Fock and density functional theory methods. In addition, the title compound's molecular energies, Mulliken-ESP-NPA-Hirshfeld charges, molecular electrostatic potential surface, Frontier orbitals and thermodynamic properties to elucidate intermolecular interactions were calculated. All the calculations in gas and solid phases were carried out using Gaussian 09 and Quantum Espresso programs. It was found that the studies of X-ray are more compatible with the calculations made in the solid phase.
Keywords: Schiff bases; X-ray; Quantum Espresso; DFT; Thermodynamic properties